2018
DOI: 10.15296/ijwhr.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Umbilical Cord Coiling Index and Prenatal Outcomes

Abstract: Objectives: This study aimed to measure the umbilical cord indices (UCIs) after birth and to determine its relationship with prenatal complications. Materials and Methods: The present analytical cross-sectional study was conducted on all the pregnant women admitted to AlZahra hospital of Rasht. After birth, the umbilical cord was measured in terms of the appearance, number of vascular coils, and umbilical cord length. In addition, the umbilical cord vascular coils index was calculated. Further, maternal and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…A study conducted by Milani et al reported insignificant differences among parity of the pregnancy across coiling indexes with a p-value of 0.26 which is in agreement with the current study p-value of 0.31 [ 18 ]. The study conducted by Patil et al tested for the association of UCI with adverse outcomes that revealed a significant difference in terms IUGR with p-value < 0.01 similar to our study findings [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted by Milani et al reported insignificant differences among parity of the pregnancy across coiling indexes with a p-value of 0.26 which is in agreement with the current study p-value of 0.31 [ 18 ]. The study conducted by Patil et al tested for the association of UCI with adverse outcomes that revealed a significant difference in terms IUGR with p-value < 0.01 similar to our study findings [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…A study done by Milani et al, found a significant difference between abnormal umbilical cord coiling index and gestational hypertension. 27 Lv et al concluded that hypercoiling of cord was found more predominantly in pre-eclampsia patients. 28 Similarly, a study done by Tripathy et al concluded that there was a significant relationship between hypocoiling of umbilical cords and pregnancy induced hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Summary of various studies done in India examining the mean aUCI ± SD is mentioned in Table 1. (Sharma et al, 2018) 0.38 ± 0.08 (Chholak et al, 2017) 0.24 ± 0.09 (Rahi and Akther, 2017) 0.20 ± 0.08 (Gaikwad and Patole, 2016) 0.19 ± 0.08 (Jain and Mathur, 2017) 0.38 ± 0.11 (Agarwal et al, 2014) 0.34 ± 0.18 (Milani et al, 2018) 0.36 ± 0.07 (Chitra et al, 2012) 0.24 ± 0.09 (Kashanian et al, 2006) 0.25 ± 0.09 (Wakpnjar et al, 2016) 0.17 ± 0.009 (Qin et al, 2002) 0.62 ± 0.2 (Ezimokhai et al, 2000) 0.26 ± 0.09 (Ercal et al, 1996) 0.20 ± 0.10 ( Degani et al, 1998) 0.44 ± 0.11 (Rana et al, 1995) 0.19 ± 0.10 Differential growth of the umbilical cord vasculature 3.…”
Section: Methodsmentioning
confidence: 99%